Sharia financial literacy: Decoding the nexus of civil Servants' investment choices - Mutiara, Nisa; Askafi, Eka; Yani, Ahmad; Aquinas, Fahmi; Herry Setyawan, Wawan (Journal of Innovation in Business and Economics, 2023)
This research explores the complex relationship between Sharia financial literacy, financial attitudes, financial satisfaction, and investment decisions in the context of Islamic economics. Utilizing path analysis with 369 civil servant respondents, this study reveals that both Sharia financial literacy and financial attitudes positively impact financial satisfaction. This implies that individuals possessing a strong understanding of Islamic finance and a positive attitude toward their finances tend to experience higher levels of financial satisfaction. Nevertheless, variations in their direct influence on investment decisions do surface. Sharia financial literacy exhibits a relatively modest direct influence on investment decisions, while financial attitudes exert a strong direct influence on investment decisions. Despite the modest direct impact of Sharia financial literacy on investment decisions, its indirect influence remains substantial.